The Role of Solubility in the Toxicity of Metal Oxide Nanoparticles - Boyadzhiev, Andrey (Université d'Ottawa | University of Ottawa, 2025)
Metal oxide nanoparticles (MONPs) represent one of the largest classes of engineered nanomaterials (ENM) in the world. As with ENM in general, MONPs present a challenge for regulatory risk assessment due to the numerous physicochemical properties impacting their toxicity. One of the most critical properties of MONPs is their solubility in biological microenvironments, affected by factors such as their surface area, surface reactivity, and chemical composition. The relative contribution of the particulate and dissolved fractions to toxicity induced by MONPs remains poorly understood. In this context, the underlying question this thesis sought to address was: what is the relative contribution of particulate and dissolved fractions to MONP induced toxicity? To address the question, this thesis employed 21st century toxicological tools in an in vitro lung epithelial model system (FE1) examining MONPs with varying solubility (including ZnO, CuO, NiO, Al2O3, TiO2). In the first approach, FE1 cells were exposed to MONPs, their microparticle analogues, and dissolved metal salts for 2 – 48 h for transcriptomic characterization. In the second approach, the genotoxic potential of the same MONPs and equivalents was assessed using two high-throughput screening assays (CometChip® and Microflow®). Finally, fluorescence darkfield hyperspectral imaging was used to determine the co-localization of a set of MONPs with lysosomes, while the impact of lysosomal dissolution / interaction on MONP toxicity was assessed by measuring changes in viability with and without co-exposure to a lysosomal acidification inhibitor. The results of the transcriptomic characterization and genotoxicity screening indicated compound-specific effects of solubility and the particulate and dissolved species on MONP toxicity; with the ‘HIF1α Signaling’ pathway being identified as a putative biomarker of response to acutely toxic MONPs. Based on microscopy analysis, all MONPs localized to lysosomes, with TiO2 MONPs showing the greatest co-localization. Out of the MONPs tested, lysosomal dissolution only contributed to the toxicity of CuO MONPs. In conclusion, adverse effects of MONPs are not captured solely by their solubility properties, raising concern that existing hazard groupings are based on oversimplified
Keywords: engineered nanomaterials; metal oxides; mechanistic toxicology; transcriptomics; genotoxicity; solubility